Chemiluminescent Probes for Activity‐Based Sensing of Formaldehyde Released from Folate Degradation in Living Mice. (27th April 2018) - Bruemmer, Kevin J.; Green, Ori; Su, Timothy A.; Shabat, Doron; Chang, Christopher J.
Abstract: Formaldehyde (FA) is a common environmental toxin that is also produced naturally in the body through a wide range of metabolic and epigenetic processes, motivating the development of new technologies to monitor this reactive carbonyl species (RCS) in living systems. Herein, we report a pair of first‐generation chemiluminescent probes for selective formaldehyde detection. Caging phenoxy‐dioxetane scaffolds bearing different electron‐withdrawing groups with a general 2‐aza‐Cope reactive formaldehyde trigger provides chemiluminescent formaldehyde probes 540 and 700 (CFAP540 andCFAP700 ) for visible and near‐IR detection of FA in living cells and mice, respectively. In particular, CFAP700 is capable of visualizing FA release derived from endogenous folate metabolism, providing a starting point for the use of CFAPs and related chemical tools to probe FA physiology and pathology, as well as for the development of a broader palette of chemiluminescent activity‐based sensing (ABS) probes that can be employed from in vitro biochemical to cell to animal models.